Integrated Islamic School Marketing Management in Indonesia: Competitive or Business Oriented? - Ikhwan, Afiful; Zukhrufin, Fina Kholij; Triyuliasari, Anisah (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
Marketing management at Integrated Islamic Schools (SIT) is important amidst the tight competition between educational institutions, so a strategy is needed that can balance business orientation, Islamic preaching values, and improving the quality of education in the digital era. This study aims to provide insight into how effective marketing management can improve the competitiveness of SIT in Indonesia while also influencing the number of registrations and stakeholder satisfaction. This study uses a qualitative descriptive approach with data collection techniques through interviews, observations, document analysis, and Focus Group Discussions (FGD). The data obtained were analyzed through the process of reduction, presentation, verification, and conclusion and validated using triangulation to ensure the validity of the findings. The results of the study show that SMPI Al-Azhaar Tulungagung has succeeded in implementing an effective educational marketing management strategy through careful branding planning, organizing resources and promotions, accepting new students, and quality control. School branding is built by prioritizing student achievement, OSIS leadership, publication of written works, and the Class Gazebo acceleration program. Resource organization is carried out by involving teachers, students, and parents in school promotion, while the promotion strategy combines digital and face-to-face media, including the parenting program (MAJELAS). The new student admission process is designed in stages to maintain quality and competitiveness. In contrast, quality control is carried out through evaluation of the quality assurance system and parental cooperation through the MoU. All of these strategies have a positive impact on parental satisfaction, strengthen the school's image, and increase the competitiveness of integrated Islamic educational institutions at the national level. The results of this study imply that planned marketing management, involving all elements of the school and integrating Islamic values, ​​​​can improve the image, competitiveness, and satisfaction of stakeholders in integrated Islamic educational institutions.